Modeling Of Infiltration Characteristics Through Hexagonal Modular Permeable Pavements Design Using Flow-3d - Arumugam, Mohd Aminur Rashid Bin Mohd Amiruddin (2012)
Modular permeable pavements have been regarded as an effective tool in helping with stormwater control. Permeable pavements are now considered an effective BMP for reducing stormwater runoff volume and peak flow. To further test the hydrologic and hydraulic responses of various permeable pavement designs, an infiltration rig consisting of newly invention Hexagonal Modular Permeable Pavement System, (HMPS) was constructed. Each pavement section covered an area of 0.313 m2 and 0.6m depth. The HMPS sections consisted of hexagonal modular with gravel fill and were underlain by gravel base layer. Exfiltrate from the permeable pavements drained via underdrains in the gravel base layer. Hydrologic differences among pavements were evaluated for surface runoff volume and total outflow volume. The effects of rainfall depth and rainfall intensity were evaluated for all hydrologic responses. HMPS significantly reduced surface runoff volumes and peak flow rates from those of asphalt. This study further focused on modelling and visualizing the changes in the permeable pavements using FLOW-3D in cooperating with laboratory experiment. The software was calibrated with the data from both laboratory and on site experiment. Velocity magnitude fields and pressure fields were observed against to infiltration characteristics in different HMPS layer thickness. Results from FLOW-3D showed that height of water were agreeable to laboratory observed data. Based upon this study, HMPS with porosity of 35% was recommended. Each unit of HMPS would consist of 10cm thick of hexagonal module; thus six vertical units would be required to make up the total thickness of the system, which would cater for 0.3cm/hour rainfall intensity.